The Influence of Celebrity Advocacy, Brand Trust, Brand Love, and Brand Respect on Brand Loyalty (Case Study on Uniqlo Brand Customers in Surabaya) - Syahrani Nur Aullia Octivanti; Nurul Azizah (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to examine the influence of celebrity advocacy, brand trust, brand love, and brand respect on brand loyalty. This research uses quantitative research methods. The sampling technique is a sampling technique of 5% of the existing population. The sample used was 105 customers of Brand Uniqlo Indonesia in Surabaya City with an age range of 20-24 years. Data collection was obtained from distributing questionnaires and analyzed by software SmartPLS 4.0 version. Based on the research results, it shows that celebrity advocacy has a significant effect on brand loyalty, brand trust has a significant effect on brand loyalty, brand love has a significant effect on brand loyalty, and brand respect has a significant effect on brand loyalty, brand trust has a significant effect on brand loyalty.